The effect of profitability in income smoothing practice with good corporate governance and dividend of payout ratio as a moderation variable - Yanti, Ni Made Yeni Witaris Asmita; Dwirandra, A.A.N.B. (International research journal of management, IT and social sciences, 2019)
One of the factors that influence income smoothing is profitability. Profitability is the ability of a company to earn profits or profits in a certain period and as a measure of the management effectiveness of a company. The variables of good corporate governance and dividend payout ratio are thought to play a role in moderating the effect of profitability on the probability of the occurrence of income smoothing practices. The sample selection method in this study used a purposive sampling method with the criteria of all companies listed on the Stock Exchange which were included in the CGPI ranking from 2012-2016 and companies that distributed dividends from 2012-2016. The sample in this study were 7 companies with 5 years of observation. The variable income smoothing practice is measured using the eckel index. The variable profitability is measured using the ROA (Return On Asset) ratio. Variables of good corporate governance are measured using the CGPI score. Dividend payout ratio variables are measured using the dividend per share formula divided by earnings per share. The analysis technique used is logistical binary regression and Moderated Regression Analysis (MRA).